Performance determinants of foreign currency bonds issued by JSE-listed companies? An indexation approach - Neethling, Sean (Department of Finance and Tax, 2024)
The number of Johannesburg Stock Exchange (JSE) listed companies that have issued foreign or hard currency denominated bonds has increased meaningfully since the global financial crisis in 2008. This broader hard currency opportunity set is primarily available to professional local investors but accessibility is largely constrained by a lack of reliable data and a representative index to assess performance. This thesis constructs hard-currency non-Rand denominated corporate bond indices using both traditional and fundamental indexation strategies to critically investigate the performance of the investable opportunity set. The constructed indices represent a first attempt to study the hard currency universe in South Africa and covers the 12-year period between 2008 and 2019. The main findings show that the constructed fundamental indices not only generate superior absolute nominal and excess returns versus a traditional market cap equivalent, but do so by taking less total, systematic and downside risk. The next substantive chapter considers the volatility of total bond returns generated by these indices. This is done using a GARCH-MIDAS framework that allows for the incorporation of data at different frequencies into the same model. The findings show that certain market and macroeconomic variables significantly affect the volatility of total returns generated by the constructed indices. Specifically, the JSE All-Share index is shown to account for approximately one third of corporate bond market volatility in the long run, which would suggest that monitoring performance at the aggregate equity index level could potentially improve the robustness of client portfolios holding corporate bond assets. The final substantive chapter builds on these conclusions by investigating the relative informational efficiency between the corporate bond and equity markets. This is done by using a VAR model to analyse the lead-lag relationship between bonds and equity issued by the same firms. The results are largely consistent with previous contributions to the literature showing that equity markets are relatively more informationally efficient and tend to lead corporate bond markets. This would suggest that equity returns are potentially predictive of future corporate bond returns and may allow professional investors to more appropriately manage risk in multi-asset portfolios.